(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Health information is the clear, concise and acute history of a patient’s life and illness written from the medical point of view. It is the data related to a person’s medical history including symptoms, diagnoses, procedures and outcomes. Thus, confidentiality of such health information is of great benefit to the patients, by providing a secured environment, while giving a full account of their illness during consultation or contact with the health service provider. Despite the ethical and legal obligations, unauthorized disclosure or access to confidential patient information has become more prevalent in today’s health care service vicinity in the reasoning of the patients. This study was therefore conducted to examine knowledge and attitude of patients’ right towards confidentiality of their health information in Bowen University Teaching Hospital (BUTCH), Ogbomosho. Descriptive survey research design was adopted in this study and convenience sampling techniques was used to select 150 respondents; while questionnaire was used for data collection. The descriptive statistics of frequency counts, percentages and inferential statistics of Pearson product moment correlation and analysis of variance were used for the analysis with the aid of statistical package for social sciences (SPSS). The finding of this study revealed that patients attending BUTCH, Ogbomosho had adequate knowledge of confidentiality of health information, while attitude was fair. However, there was a negative relationship between knowledge and attitude of patients attending BUTCH towards confidentiality of their health information (r=-0.007, p>0.05). It was concluded therefore, that patients attending Bowen Teaching Hospital, Ogbomosho had adequate knowledge and fair attitude towards confidentiality of their health information. It was suggested among other therefore; that the management of Bowen Teaching Hospital, Ogbomosho should collaborate with the government, non-governmental organisations as well as other stakeholders to organize effective health education programmes for patients on the importance of adequate knowledge and positive attitude towards confidentiality of their health information.